Colorado's secondary school programs of agricultural education: perceptions of sustainability - Enns, Kellie Jo, author; Lehmann, Jean P., advisor (Colorado State University. Libraries, 2008)
Agricultural education (Ag Ed) is faced with unique challenges; competition for scarce resources, teacher retention, and quality programmatic offerings are dilemmas within the profession. A rapidly changing agriculture industry and societal shift away from agrarian lifestyles complicates the Ag Ed culture. These challenges indicate it is a prudent time to study sustainability of Ag Ed in Colorado. The purpose of the study was fourfold: first to understand if Colorado Ag Ed programs are perceived sustainable; second, to determine the characteristics of important resources in agricultural education; third, to determine the association of resources to program sustainability; and finally, to understand demographics that might predict sustainability. Knowledge of sustainability may help policy makers to develop models for programs consistent with state and national strategic growth initiatives. Perceptions were gathered from three groups of Ag Ed stakeholders in the 2007-2008 school-year: teachers (n = 96), administrators (n = 64) and community members (n = 65). Agricultural education in Colorado is perceived to be sustainable. Sustainability was ranked on a 10 point scale (1 = Very Sustainable to 10 = Very Unsustainable), M = 2.32, N = 204, SD = 1.37. Program resources were characterized according to the perceptions of stakeholders. Utilizing Spearman's Rho statistic, the effectiveness of Ag Ed resources of Organization and Instructional Content (rs = .399), FFA and Leadership Development (rs = .305), SAE and Experiential Learning (rs = .403), the Agriculture Teacher (rs = .337), Program Management (rs = .453) and Program Support (rs = .454) were positively correlated to sustainability. The Kruskal-Wallis test determined if differences existed in the three stakeholder groups perceptions of sustainability. The groups showed no significant differences regarding perception of Ag Ed program sustainability, χ2 (2, N = 204) = 4.875, p = .087. Demographic data and sustainability perceptions were utilized in a simultaneous multiple regression equation. The combination of variables to predict sustainability was statistically significant, F(5,134) = 7.167, p < .000. Demographic characteristics of School Enrollment, Ag Ed Enrollment, and Ag Industry Outlook significantly predict sustainability when all variables are included. The adjusted R2 value was .172. This indicates that this model explains about 17 percent of the variance in sustainability.
Keywords: agriculture teachers; Colorado; FFA and leadership development; Future Farmers of America; organization and instructional content; program support and management; SAE and experiential learning; secondary school; supervised agricultural experience; total program; agricultural education; secondary schools; perceptions; sustainability